Stereotactic body radiotherapy for moderately central and ultra-central oligometastatic disease: Initial outcomes. (March 2020) - Cooke, Rosie; Camilleri, Philip; Chu, Kwun-Ye; O'Cathail, Séan M.; Robinson, Maxwell; Van Den Heuvel, Frank; Hawkins, Maria A.
Highlights: SBRT can be safely delivered to central and ultra-central thoracic oligometastases. Adhering to OAR dose constraints resulted in low acute and late toxicity rates. PTV coverage compromise does not appear to significantly affect control or survival. Abstract: Background: Delivery of SBRT to central thoracic tumours within 2 cm of the proximal bronchial tree (PBT), and especially ultra-central tumours which directly abut the PBT, has been controversial due to concerns about high risk of toxicity and treatment-related death when delivering high doses close to critical mediastinal structures. We present dosimetric and clinical outcomes from a group of oligometastatic patients treated with a risk-adapted SBRT approach. Methods: Between September 2015 and October 2018, 27 patients with 28 central thoracic oligometastases (6 moderately central, 22 ultra-central) were treated with 60 Gy in 8 fractions under online CBCT guidance. PTV dose was compromised where necessary to meet mandatory OAR constraints. Patients were followed up for toxicity and disease status. Results: Mandatory OAR constraints were met in all cases; this required PTV coverage compromise in 23 cases, with V100% reduced to <70% in 11 cases. No acute or late toxicities of Grade ≥ 3 were reported. One and 2 year in-field control rates were 95.2% and 85.7% respectively, progression-free survival rates were 42.8% and 23.4% respectively, and overall survival rates were 82.7% and 69.5% respectively. No significant differences were seen in control or survival rates by extent of PTV underdosage or between moderately and ultra-central cases. Conclusion: It appears that compromising PTV coverage to meet OAR constraints allows safe and effective delivery of SBRT to moderately and ultra-central tumours, with low toxicity rates and high in-field control rates. This treatment can be delivered on standard linear accelerators with widely available imaging technology.